2019
DOI: 10.3390/lubricants7110095
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Surface Texturing in Tribology—Current Knowledge and Future Perspectives

Abstract: Surface texturing has been frequently used for tribological purposes in the last three decades due to its great potential to reduce friction and wear. Although biological systems advocate the use of hierarchical, multi-scale surface textures, most of the published experimental and numerical works have mainly addressed effects induced by single-scale surface textures. Therefore, it can be assumed that the potential of multi-scale surface texturing to further optimize friction and wear is underexplored. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 230 publications
2
94
0
Order By: Relevance
“…Modification of surface topography is one of the main aims of surface engineering. By producing aperiodic or periodic patterns at the micro and/or nano scale, surface roughness changes, and thus may influence wetting behavior of liquids [1][2][3][4][5][6][7][8][9][10][11], lubrication [12][13][14], friction and wear [15,16], cell adhesion and biocompatibility [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Modification of surface topography is one of the main aims of surface engineering. By producing aperiodic or periodic patterns at the micro and/or nano scale, surface roughness changes, and thus may influence wetting behavior of liquids [1][2][3][4][5][6][7][8][9][10][11], lubrication [12][13][14], friction and wear [15,16], cell adhesion and biocompatibility [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The total energy efficiency could be significantly increased by utilizing new technologies such as surface modifications (Holmberg and Erdemir [5]). This can be achieved, for instance, by applying amorphous carbon (DLC) coatings (Kalin et al [6], Erdemir and Donnet [7]) or discrete microtextures (Gropper et al [8], Gachot et al [9][10][11]) onto the rubbing surfaces of lubricated tribological sliding contacts. Both approaches have been intensively investigated in the literature within various theoretical and experimental studies ranging from boundary (Pettersson and Jacobson [12]), to mixed (Löffler et al [13], Borghi et al [14]), as well as full-film hydrodynamic (Etsion [15], Pawlus et al [16,17]) and elastohydrodynamic lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…The textures produced often consist of periodically repeating structures (objects). LST uses pulsed lasers for the removing or moving of material by ablation or melting processes and scanning optical systems or translation and rotation stages for the movement of the laser beam on the workpiece on predefined trajectories to form the desired surface structure [1,2]. When using ultrafast lasers, LST has almost no heat-affected zone and can be applied to transparent materials as well [3].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma and particle shielding effects (2) are the attenuation or reflection of the laser pulse by plasma and ablated material produced by the laser pulse or for high repetition rates by the previous laser pulse. Mao et al [13] observed different depths and shapes of craters formed by picosecond laser ablation in various gas mediums and its pressures.…”
Section: Introductionmentioning
confidence: 99%